My little pony : Izzy comes home - Roth, Megan; Garbowska, Agnes (New York : HarperAlley, an imprint of HarperCollinsPublishers, 2022)
Based on the all-new animated series, the My Little Pony friends go on a new adventure in this I Can Read Comic. Featuring a bold new comic style and easy-to-read text , this Level One I Can Read Comic is perfect for everypony! When Izzy tells Sunny stories about growing up in Bridlewood, Sunny suggests visiting Izzy's favorite places in her hometown. Although Izzy loves Bridlewood, the friends ultimately discover that home isn't a place, it's being with your family. My Little Pony: Izzy Comes Home is a Level One I Can Read Comic, which means it's perfect for shared reading with young readers new to graphic novel storytelling.
Level 2.
Keywords: Ponies -- Juvenile fiction; Friendship -- Juvenile fiction; Romans, nouvelles, etc. pour la jeunesse; Friendship; Ponies; Comics (Graphic works); Graphic novels; Comics (Graphic works); Fiction; Graphic novels; Juvenile works; Comics (Graphic works); Graphic novels